Kerjasama Pemerintah Kota Pekalongan dengan Juru Parkir dalam Pengelolaan Parkir di Tepi Jalan Umum Tahun 2013-2015 - Firmanda, Muhammad Aries; Adnan, Muhammad (Journal of Politic and Government Studies, 2017)
ABSTRACTThe cooperation of managing parking on streetc by the Government of Pekalongan City and parkers departing from regional autonomy. The government has the authority to manage the potential in their own areas.This can be undertaken in collaboration with the private sector. The Goal of roadside parking management cooperation common in Pekalongan is to carry out the mandate of the Regional Regulation No. 21 Year 2011 on retribusion parking on street. This system replaces the old system by the ticketing and auction to third parties. Cooperation is intended to optimize the management of retribution.This study uses qualitative descriptive method to describe the system of parking on street management cooperation common in Pekalongan.The data used was taken from in-depth interviews, field notes, and study documents.Cooperation management of parking on street is technically done by the Department of Transportation in Pekalongan and parkersr with the contract model each year from 2013 to 2015 targeted Rp700.000.000. The target is always achieved and fulfilled. Then the management of parking lots for the better with their letter of agreement that binds the parties working together.Cooperation management of parking on street is not free from problems. Limited human resources on the Department of Transportation to control is not optimal.As a result there is dishonesty in cooperationof management parking on street. The solution to this problem limited to a reprimand and termination of cooperation.From the research that has been done, this cooperation was successful because the targets have been achieved.But still need the arrangement of the methodology determination of potential retribution.Keywords: Cooperation, Parking Management, Local Government, Parkers.